Chronic Cough in Otorhinolaryngologic Routine - Neto, Francisco Xavier Palheta; Ramos, Camilo Ferreira; Tavares e Silva, Amanda Monteiro; dos Santos, Karla Araújo Nascimento; de Azevedo, Ana Carolina Guimarães; Palheta, Angélica Cristina Pezzin (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The chronic cough is sometimes manifested as an imprecise symptom, but of great importance for both the diagnosis and the prognosis. In an otorhinolaryngologic approach, several illnesses that can occur with it can be numbered, including 2 of the 3 main causes of chronic cough.Objective: To identify the main otorhinolaryngologic diseases showing the chronic cough as one of their manifestations.Method: A literature's revision was performed in several scientific articles, specialized books and consultation in Birene and Scielo databases.Literature's revision: cough production in the upper airways is usually associated with an inflammatory reaction by stimulating sensitive receptors of these areas or by mechanic stimulus. The main cause of the chronic cough in the otorhinolaryngology day-to-day is the post-nasal drip, gathering together by itself 02 of the most common diseases: rhinitis and sinusitis. Laryngitis as a result of gastroesophageal reflux (GER) stands out in the index of chronic cough etiology, but it is not as severe as GER . Neoplasias are also somewhat frequent causes of cough, and the difficulty in diagnosing the cough cause is common in this disease group. Motility disorder, laryngeal irritation persistence, parasitic disease and injuries by inhalation of toxic products were also found as a cause of cough for longer than 03 months.Conclusion: Chronic cough is a frequent and important finding in otorhinolaryngology and cannot be underestimated, and a careful anamnesis is the best way to determine the etiology and perform a correct treatment for the patient's disease.
Keywords: cough; rhinitis; sinusitis; gastroesophageal reflux; otorhinolaryngopathies